The Influence Of Plyometric Training On 50-Meter Freestyle Swimming Speed At Adyas Aquatics Club Sumedang - Kasibah Suriadiningrat, Rd Naufal; lengkana, Anggi setia; Encep Sudirjo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to determine the effect of plyometric training to increase 50 meter freestyle swimming speed at the Adyas Aquatik Sumedang club. Plyometric training is one of the important exercises to increase swimming speed for athletes. One Group Pre-test Post-test Design research method to determine differences before and after being given certain treatments. The sample used in this study using non probability sampling type purposive sampling or sampling technique with certain considerations, aged 12-14 years with a total of 12 athletes. Using the 50 meter speed test as an instrument in the study. The results of the normality test data processing produced a significant pretest of 0.267 while the posttest was 0.671. From this data it is interpreted that the normality test is normally distributed, because the significance is> 0.05. The homogeneity test was carried out which resulted in a significance of 0.797. From these data it can be interpreted that the homogeneity test is homogeneous. Then the Paired Sample T-test was conducted to determine the effect produced with a value of 0.005. The study found that 50-meter freestyle swimming (after using plyometric training) increased more than the initial test. This shows that plyometric training can increase the speed of 50-meter freestyle swimming at the Adyas Aquatik Sumedang club.